Embodied Queer Muslim Resistance: Negotiating Islam, Gender, and Sexuality from Pesantren - Nanda Tsani Azizah (Elkuator Research and Publication, 2025)
This article examines the intersections of queerness, faith, and resistance in the lived narratives of queer Muslims in Indonesia, with particular attention to the pesantren (Islamic boarding school) context. While dominant global narratives of LGBTQ rights have emerged from Western experiences—centered on visibility politics, Pride parades, and legal recognition—this study interrogates how such frameworks can marginalize queer Muslims whose lives are shaped by different cultural, religious, and political realities. Drawing from narrative interviews with three queer Muslims and one ally who spent years in pesantren environments (boarding house where santri or students learning Islamic teachings, etc.; a cottage), this research employs a decolonial and intersectional lens to highlight how participants navigate Islam, gender, and sexuality in their everyday lives. The findings show that pride and resilience among queer Muslims cannot be understood through Western liberal models alone but are expressed through alternative practices of belonging, storytelling, and religious embodiment. By engaging Melissa M. Wilcox’s concept of queer religiosities alongside decolonial critiques, this article argues that four Indonesian queer Muslims i.e. Ji, Ro, Durga, and Fik contribute new epistemologies that challenge the universality of Western queer theory and religious studies. Ultimately, the study underscores the need to provincialize dominant frameworks and recognize the multiplicity of queer life-worlds in the Global South.